Identification of Germinal Center B Cells in Blood from HIV-infected Drug-naive Individuals in Central Africa - Lydie Béniguel; Evelyne Bégaud; Fabrice Cognasse; Philippe Gabrié; Christophe D. Mbolidi; Odile Sabido; Mary A. Marovich; Christiane deFontaine; Anne Frésard; Frédéric Lucht; Christian Genin; Olivier Garraud (Clinical and Developmental Immunology)
To better understand the pathophysiology of B cell populations—the precursors of antibody secreting cells—during chronic human immunodeficiency virus (HIV) infection, we examined the phenotype of circulating B cells in newly diagnosed Africans. We found that all African individuals displayed low levels of naive B cells and of memory-type CD27+ B cells, and high levels of differentiated B cells. On the other hand, HIV-infected African patients had a population of germinal center B cells (i.e. CD20+, sIgM-, sIgD+, CD77+, CD138±), which are generally restricted to lymph nodes and do not circulate unless the lymph node architecture is altered. The first observations could be linked to the tropical environment whereas the presence of germinal center B cells may be attributable to chronic exposure to HIV as it is not observed in HIV-negative African controls and HAART treated HIV-infected Europeans. It may impact the management of HIV infection in countries with limited access to HIV drugs and urges consideration for implementation of therapeutic vaccines.